HOW SPORTS CONTRIBUTE TO FOSTERING LEADERSHIP SKILLS IN STUDENTS - Numonova, Jayrona G‘olibjon qizi (Educational Research in Universal Sciences, 2024)
This article explores the ways in which sports can contribute to the development of leadership skills in students. It examines the various aspects of sports, such as teamwork, discipline, and resilience, that can help students develop important leadership qualities. The article also discusses the role of coaches and mentors in guiding students to become effective leaders both on and off the field. Additionally, it highlights the transferable nature of leadership skills learned through sports, which can have a positive impact on students’ academic and professional careers. Overall, the article emphasizes the valuable role that sports play in fostering leadership skills in students and the importance of incorporating sports programs into educational curriculums.